Pengaruh Metode Kooperatif Tipe CIRC Terhadap Kemampuan Menulis Cerpen Siswa Kelas XI - Wulandari, Putri; Maulidah, Tsalitsatul; Hardiana, Maulidia Tifani Alfin Nur (Jurnal Simki Pedagogia, 2021)
This Study aims to determine the effect of the CIRC type cooperative method on the ability to write short stories for class XI students. This Type of quantitave research uses a quasi-experimental method with a pretest-posttest control group design. Data analysis techniues used include descriptive analysis, normality test, homogeneity test, t-test, and hypothesis testing. The results of this study indicate an increase in student’s short story writing skills. In the pretest score for writing short stories, student obtained an average score of 14.0, and increase in the posttest score with an average of 22.3. This proves that there is a significant effect between the CIRC type cooperative method on the ability to write short stories for class XI student.